Wandering spleen presenting as gastric mass: A rare case - Rane, Sharada Raju; Bhatia, Varsha Omprakash; Devkate, Ujjwal (Indian Journal of Case Reports, 2018)
Wandering or ectopic spleen is a rare condition in which spleen is located outside its normal location. Wandering spleen is an incidental finding with a reported incidence of